Absolute quantitative MR perfusion and comparison against stable‐isotope microspheres. Issue 6 (8th February 2019) - Jeong, Yong I.; Christoforidis, Gregory A.; Saadat, Niloufar; Kawaji, Keigo; Cantrell, Charles G.; Roth, Steven; Niekrasz, Marek; Carroll, Timothy J.
Abstract : Purpose: This work sought to compare a quantitative T1 bookend dynamic susceptibility contrast MRI based perfusion protocol for absolute cerebral blood flow (qCBF) against CBF measured by the stable‐isotope neutron capture microsphere method, a recognized reference standard for measuring tissue blood flow, at normocapnia, hypercapnia, and in acute stroke. Methods: CBF was measured in anesthetized female canines by MRI and microspheres over 2 consecutive days for each case. On day 1, 5 canines were measured before and during a physiological challenge induced by carbogen inhalation; on day 2, 4 canines were measured following permanent occlusion of the middle cerebral artery. CBF and cerebrovascular reactivity measured by MRI and microsphere deposition were compared. Results: MRI correlated strongly with microspheres at the hemispheric level for CBF during normo‐ and hypercapnic states ( r 2 = 0.96), for individual cerebrovascular reactivity ( r 2 = 0.84), and for postocclusion CBF ( r 2 = 0.82). Correction for the delay and dispersion of the contrast bolus resulted in a significant improvement in the correlation between MRI and microsphere deposition in the ischemic state ( r 2 = 0.96). In all comparisons, moderate correlations were found at the regional level. Conclusion: In an experimental canine model with and without permanent occlusion of the middle cerebral artery, MRI‐based qCBF yielded moderate to strong correlations for absolute quantitative CBF and cerebrovascular reactivity measurements during normocapnia and hypercapnia. Correction for delay and dispersion greatly improved the quantitation during occlusion of the middle cerebral artery, underscoring the importance for this correction under focal ischemic condition.